The sun is also a star - Yoon, Nicola; Iaconis, T. (UK : Corgi Books, 2016)
"Two teens--Daniel, the son of Korean shopkeepers, and Natasha, whose family is here illegally from Jamaica--cross paths in New York City on an eventful day in their lives--Daniel is on his way to an interview with a Yale alum, Natasha is meeting with a lawyer to try and prevent her family's deportation to Jamaica--and fall in love".
Keywords: Fate and fatalism -- Juvenile fiction; Immigrants -- Juvenile fiction; Illegal aliens -- Juvenile fiction